Deep Eutectic Solvents as Media for the Prebiotic DNA-Templated Synthesis of Peptides - Núñez-Pertíñez, Samuel; Wilks, Thomas R. (Frontiers in Chemistry, 2020)
Translation of genetic information into peptide products is one of the fundamental processes of biology. How this occurred prebiotically, in the absence of enzyme catalysts, is an intriguing question. Nucleic acid-templated synthesis (NATS) promotes reactions by bringing building blocks tethered to complementary DNA strands into close proximity and has been shown to enable peptide synthesis without enzymes – it could therefore serve as a model for prebiotic translation of information stored in nucleic acid sequences into functional peptides. The decomposition of highly reactive DNA adapters has so far limited the effectiveness of NATS, but these studies have been performed exclusively in aqueous solution. Deep eutectic solvents (DESs) have been proposed as a feasible solvent for prebiotic replication of nucleic acids, and here are studied as media for prebiotic translation using NATS as a model. DESs are shown to enhance the stability of DNA-conjugated activated esters, the precursors of peptides. However, this enhanced stability was coupled with decreased amine reactivity that hampered the formation of peptide bonds in DESs . These properties are exploited to demonstrate the storage of DNA-conjugated activated esters in a DES followed by transfer into aqueous buffer to activate the NATS of peptides “on demand”. These findings, together with the reported functions of DESs in prebiotic processes, shed light on how DESs could have facilitated the nonenzymatic translation of genetic information into functional peptides on the early Earth.